Pengaruh Penggunaan Media Menghitung dengan Stik Ice Cream Terhadap Hasil Belajar Matematika Peserta Didik Kelas II - Nurfajriah, Nurfajriah; Rosdiana, Rosdiana; Basam, Fajri (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2023)
The objectives of this research are 1) Describe the results of Mathematics learning before using ice cream stick media for class II students at MI Ulil Albab Simpasai. 2) Describe the results of Mathematics learning after using ice cream stick media for class II students at MI Ulil Albab Simpasai. 3) Analyzing the influence of mathematics learning outcomes using ice cream sticks on class II students at MI Ulil Albab Simpasai. The type of research used in this research is pre-experimental design research with a one group pretest-post test type design. Based on the results of descriptive analysis of student learning outcomes before using ice cream stick media in class II MI Ulil Albab, they obtained a maximum score of 60 and a minimum of 40 with an average of 49.64 and the results of descriptive analysis of student learning outcomes after using the media Ice cream sticks obtained a maximum score of 95 and a minimum of 50 with an average of 79.64. Based on the results of descriptive analysis and the normalized gain test, the results showed that the use of ice cream stick media had a significant effect on student learning outcomes with an average value of 0.59 or n-gain >0.3 in the medium category.